Narrative Analysis of Entertainment World Criticism on Pretty Boys Film - Rashid Ridha; Poppy Febriana (Indonesian Journal of Cultural and Community Development, 2022)
Film is a product of innovation from the media. In the film there are educational values, information, persuasion and entertainment that have meaning for the viewer. Films can also be a means for filmmakers to convey messages in the form of storylines and then turn them into scenes in the narrative. The researcher discusses the analysis of narrative and dialogue in the film "Pretty Boys". this film highlights the behavior of the homeland entertainment industry which places kemayu traits in men, as selling the television industry to boost ratings, in the film also shows behavior that is less prosperous for their talents. This type of research uses a qualitative method of narrative analysis using the actan model proposed by Algirdas Greimas. The characters in the narrative occupy their respective positions and functions which are divided into six actants, namely, sender, subject, object, helper, opponent, receiver. From the results of the analysis above, it can be seen that the structure of the actants in the Pretty Boys film has fulfilled all the stages. The results of the presentation show that the welfare of talent in the entertainment world is greatly sacrificed even though the program rating is already high for the benefit of the television station itself. The results of the analysis also show that Anugerah's character in this film plays an important role in moving the story. Anugerah's character actor always appears in every scene in this film. This shows that the welfare of talent in the entertainment world is being sacrificed even though the program rating is already high for the benefit of television stations. The suggestion that the researcher wants to give about the results of this study is that people do not assume that the entertainment world workers are always happy as shown on television.